Primary and Secondary Sexual Characteristics of Kuhli Loach (Pangio kuhlii) - Budi, Darmawan Setia; Restanti, Maya; Suciyono, Suciyono; Müller, Tamás; Kenconojati, Hapsari; Mubarak, Ahmad Shofy (Jurnal Medik Veteriner, 2024)
Kuhli loach (Pangio kuhlii) a popular ornamental freshwater fish species with economic potential, originating from Sumatra, Kalimantan, Java, and Malaysia. The kuhli loach's appeal lies in its vibrant colors and distinctive eel-like body. This study aims to explores the sexual primary and secondary characteristics of the kuhli loach. Conducted at Universitas Airlangga in Banyuwangi, Indonesia, the study involved a thorough analysis of 50 kuhli loaches, evenly split between males and females. Morphological observations revealed significant differences (p < 0.05), such as the elongated body and expanded abdominal region in females, suggesting adaptations for reproduction. Internal examinations, including peritoneal dissections and histological analysis, unveiled distinct stages of spermatogenesis in males and ovarian development in females, providing insights into the reproductive cycle. Meristic and morphometric analyses identified noteworthy differences in pectoral fin rays, suggesting potential roles in reproductive behavior, while other traits exhibited similarity between genders. This study contributes to the understanding of kuhli loach ecology and reproductive biology, highlighting the importance of addressing sustainability concerns arising from the continuous exploitation of wild populations. This study serves as a foundational step towards advancing reproductive improvement in fish and supports the conservation of this unique ornamental fish species, with implications for aquaculture practices and economic considerations.